Immunological and virological consequences of patient-directed antiretroviral therapy interruption during chronic HIV-1 infection - Burton, CT (Blackwell Science Inc, 2005)
Increasing numbers of patients are choosing to interrupt highly active antiretroviral therapy (HAART). We describe the effect of patient-directed treatment interruption (PDTI) on plasma viral loads (pVL), proviral DNA (pDNA), lymphocyte subsets and immune responses in 24 chronically HIV-1 infected individuals. Patients were divided into group A with pVL > 50 copies/ml and group B with pVL < 50 copies/ml, prior to the PDTI. pVL rose significantly in group B during the first month off HAART and was associated with a significant decrease in CD4 T-cell count. At baseline there was a significant difference in HIV-1 pDNA levels between groups A and B, however, levels significantly increased in group B, but not in group A during PDTI becoming equivalent after 1 month PDTI. We have previously shown no increase in pDNA over the time of substitution in patients switching HAART regimens despite a small rebound in pVL. These observations indicate that to protect low pDNA levels PDTI should be discouraged and that changing regimen at the first sign of failure should be advised where possible. Only transient, no longer than 4 week, HIV-1-specific responses were observed during PDTI in 5/24 patients, 2 from group A and 3 from group B. The low numbers of responders and the transient nature of the anti-HIV-1 immune responses do not favour the auto-vaccination hypothesis.